A contemporary picture of the burden of death and disability in Indian adolescents: data from the Global Burden of Disease Study. (28th June 2017) - Joshi, Rohina; Alim, Mohammed; Maulik, Pallab K; Norton, Robyn
Abstract: Background: Adolescents (10–19 years old) comprise a fifth of the Indian population (253.2 million), yet there is very little published information about the burden of disease and injury for this age group. This paper aims to provide a contemporary picture of the leading causes of death and disability for Indian adolescent girls and boys for 2013, and changes in deaths and disability between 1990 and 2013. Methods: Data from the Global Burden of Disease (GBD) study for India, for the years 1990 and 2013, were accessed. Data were categorized into two age groups: 10 to 14 years (younger adolescents) and 15 to 19 years (older adolescents) and analysed separately for girls and boys. Results: The study shows that for both younger and older adolescent boys and for older adolescent girls, non-communicable diseases (NCDs) and injuries are responsible for a greater number of deaths and disability-adjusted life-years (DALYs) than communicable diseases. Communicable diseases are still important causes of death and disability for young adolescents. Among older adolescents there is an increasing burden of death and disability due to self-harm, road traffic injuries, fire- and heat-related injuries and mental disorders such as depressive disorders. Conclusions: Although strategies to reduce the burden of communicable diseases among adolescents must continue to be an important focus, innovative, evidence-based strategies aimed at reducing the growing burden of NCDs and injuries must be elevated as a priority.